Integrated optimization of train scheduling and maintenance planning on high-speed railway corridors. (September 2019) - Zhang, Chuntian; Gao, Yuan; Yang, Lixing; Kumar, Uday; Gao, Ziyou
Highlights: A new train scheduling problem is studied with maintenances planning. State variables are introduced to formulate a MILP model. Three operation modes are considered in the model. The proposed model and method are tested on real-world instances. Abstract: Regular maintenances on high-speed railway facilities are performed in every night in China, and during regular maintenances, high-speed railway is not available for the sunset-departure and sunrise-arrival trains (SDSA-trains). In order to reduce the influence of regular maintenances on SDSA-trains, three operation modes are used in practice, which mainly consist of route selections between high-speed railway and normal-speed railway. In this paper, we use some linearization techniques to formulate a mixed integer linear programming (MILP) model to identify the operation modes and the timetable of SDSA-trains, by integrating the time window selection of regular maintenances on high-speed railways. The objective of the model is to minimize the total travel time of SDSA-trains. In the formulation of the model, we introduce state variables to indicate whether a train is running on high-speed railway or not, which makes it conveniently express the selection of operation modes. Based on the real data of Beijing-Guangzhou high-speed and normal-speed railway corridors in China, numerical experiments are carried out to test the proposed model and optimization method.